Nursing in Primary Health Care: association between leadership, psychological capital, and burnout implications - Debora Paulino da Silva Almeida; Paula Vitali Miclos (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to verify the association between authentic leadership and burnout syndrome in Primary Health Care nursing professionals and analyze the relationship between positive psychological capital and burnout syndrome in subordinate nursing professionals. Methods: a field, descriptive-exploratory, cross-sectional study with a quantitative approach, developed with the nursing team, in Basic Health Units in the city of São Paulo, with the application of the sociodemographic questionnaires, Burnout Characterization Scale [Escala de Caracterização do Burnout], Authentic Leadership Questionnaire and Psychological Capital Questionnaire. Results: in leaders' perception, there was no evidence of significant associations between burnout and authentic leadership scales. There was a significant negative association of the burnout scale dimensions with the leadership dimensions regarding the subordinates. There was evidence of significant negative associations in the burnout scores with the scores of the psychological questionnaire dimensions. Conclusions: in nursing, burnout is associated with authentic leadership and psychological capital.